Psoriatic arthritis: treatment strategies using biologic agents - C. Palazzi; S. D'Angelo; I. Olivieri (PAGEPress Publications, 2012)
The traditional management of psoriatic arthritis (PsA) includes NSAIDs, corticosteroids and DMARDs. Advancement in the knowledge of the immunopathogenesis of PsA has been associated with the development of biologic agents which have revolutionized the management of the disease. Among biologics drugs, there are the 4 currently availablee anti-TNFα blocking agents (etanercept, infliximab, adalimumab and golimumab) which are more effective than traditional DMARDs on symptoms/signs of inflammation, quality of life, function, and in inhibiting the progression of the structural joint damage. Despite of the high cost, TNF inhibitors are costeffective on both the musculoskeletal and skin manifestations of psoriatic disease.